2019
DOI: 10.1093/ofid/ofz452
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Treatment Failure for Hip and Knee Prosthetic Joint Infections in the Setting of 1- and 2-Stage Exchange Arthroplasty: A Multicenter Retrospective Cohort

Abstract: BackgroundProsthetic hip and knee joint infections (PJIs) are challenging to eradicate despite prosthesis removal and antibiotic therapy. There is a need to understand risk factors for PJI treatment failure in the setting of prosthesis removal.MethodsA retrospective cohort of individuals who underwent prosthesis removal for a PJI at 5 hospitals in Toronto, Canada, from 2010 to 2014 was created. Treatment failure was defined as recurrent PJI, amputation, death, or chronic antibiotic suppression. Potential risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 38 publications
3
45
1
3
Order By: Relevance
“…Currently, two-stage exchange arthroplasty is considered the best treatment option, with success rates ranging from 50% to over 90% [ 13 , 14 ]. In a significant percentage of patients, however, final reimplantation cannot be completed due to the poor health of the patient or persistent infection, which increases the risk of therapeutic failure and mortality [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, two-stage exchange arthroplasty is considered the best treatment option, with success rates ranging from 50% to over 90% [ 13 , 14 ]. In a significant percentage of patients, however, final reimplantation cannot be completed due to the poor health of the patient or persistent infection, which increases the risk of therapeutic failure and mortality [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Uçkay and Bernard [ 32 ] reported similar success rates when treating PJIs caused by GPC or GNB. In contrast, several studies have linked GNB-associated PJI with high failure rates [ 16 ]. In our study, surgical options using DAIR had no impact on treatment outcomes, but XDR-PJI was independently associated with poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term remission of PJI following treatment was defined as the absence of clinical, laboratory and radiological symptoms of infection at the last medical follow-up (with a minimum follow-up point of one year). Therapeutic failure was defined as infection recurrence at a previously controlled site; requirement for new surgery, a second course of antimicrobial therapy, chronic antibiotic suppression, excision arthroplasty or limb amputation, or death within the follow-up period [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Each of these procedures has its advantages and disadvantages. A multicenter, retrospective cohort study performed by Kandel et al reported a combined treatment failure rate of 24.8 % at two years following OSE or TSP; at four years, the failure rate for OSE was reported as 36 % and 32 % for TSP [ 5 ].…”
Section: Discussionmentioning
confidence: 99%